2015
DOI: 10.1051/0004-6361/201424504
|View full text |Cite
|
Sign up to set email alerts
|

LOFAR sparse image reconstruction

Abstract: Context. The LOFAR (LOw Frequency ARray) radio telescope is a giant digital phased array interferometer with multiple antennas distributed in Europe. It provides discrete sets of Fourier components of the sky brightness. Recovering the original brightness distribution with aperture synthesis forms an inverse problem that can be solved by various deconvolution and minimization methods. Aims. Recent papers have established a clear link between the discrete nature of radio interferometry measurement and the "comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 59 publications
0
78
0
Order By: Relevance
“…Furthermore, previous studies of sparse image reconstruction techniques have shown that regularization with ℓ 1 +wavelet/curvelet transformation is also a promising approach (e.g., Li et al 2011;Carrillo et al 2012Carrillo et al , 2014Garsden et al 2015;Dabbech et al 2015). We will test these sparse regularizations in a forthcoming paper.…”
Section: Other Sparse Regularization For Smoothed Imagesmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, previous studies of sparse image reconstruction techniques have shown that regularization with ℓ 1 +wavelet/curvelet transformation is also a promising approach (e.g., Li et al 2011;Carrillo et al 2012Carrillo et al , 2014Garsden et al 2015;Dabbech et al 2015). We will test these sparse regularizations in a forthcoming paper.…”
Section: Other Sparse Regularization For Smoothed Imagesmentioning
confidence: 99%
“…However, it is not straightforward to extend the idea for the problems with multiple regularization functions. For another example, Garsden et al (2015) proposes another heuristic method to determine the regularization parameters on ℓ 1 -regularization on the wavelet/curvelet-transformed image by estimating its noise level on each scale, which is successful. However, the method would not work for all types of regularization functions.…”
Section: Determination Of Imaging Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…A greedy alternative to the minimization of a regularized cost function was proposed by Dabbech et al (2015). Sparse image representations using wavelet dictionaries has indisputably shown substantial improvement with respect to classical CLEAN-based approaches, as demonstrated by Garsden et al (2015) using LOFAR data and Dabbech et al (2018) using VLA data. The price to pay is an increased computational cost and a lot of effort has gone into designing scalable methods able to cope with large data sets.…”
Section: Introductionmentioning
confidence: 99%